Winter Oilseed Rape: Agronomic Management in Different Tillage Systems and Seed Quality - Mateusz Sokólski; Dariusz Załuski; Artur Szatkowski; Krzysztof Józef Jankowski (Agronomy, 2023)
A three-year study was conducted to analyze agronomic management in the production of winter oilseed rape (WOSR) under different tillage systems. A field experiment was conducted at the University’s Agricultural Experiment Station in Bałcyny (north-eastern Poland), in three growing seasons (2016/2017, 2017/2018, and 2018/2019). The experiment had a 35–2 resolution III fractional factorial design with five fixed factors that were tested at three levels of intensity. The experimental factors were: A—tillage: (A0) strip-till, (A1) low-till, (A2) conventional tillage; B—weed control: (B0) pre-emergent, (B1) foliar, (B2) sequential; C—growth regulation: (C0) none, (C1) in fall, (C2)—in fall and spring; D—rate of nitrogen (N) fertilizer applied in spring: (D0) 160, (D1) 200, (D2) 240 kg ha−1; and E—rate of sulfur (S) fertilizer applied in spring: (E0) 0, (E1) 40, (E2) 80 kg ha−1. The crude fat (CF) content of WOSR seeds was highest in the strip-till system (498 g kg−1 dry matter, DM), and the total protein (TP) content of seeds was highest (196 g kg−1 DM) in low-till and conventional tillage systems. The content of neutral detergent fiber (NDF) was higher in seeds harvested from strip-till and low-till systems than from the conventional tillage system. The seeds of WOSR plants grown in the conventional tillage system accumulated more (by 0.4%) polyunsaturated fatty acids (PUFAs) and less (by 0.5–0.6%) monounsaturated fatty acids (MUFAs). An increase in the N rate from 160–200 to 240 kg ha−1 decreased the CF content (495 vs. 484 g kg−1 DM) and increased the TP content of seeds (191 vs. 199 g kg−1 DM). Sulfur fertilization induced a 34% increase in glucosinolate (GLS) concentrations in WOSR seeds, mainly by enhancing the biosynthesis of alkenyl GLS (by 39%).